Managing Consumer Loyalty in the Pharmaceutical Market of a Metropolis - Olga Pashanova (Journal of Global Pharma Technology, 2019)
The article presents the results of a study of a complex of factors that determine consumer behavior in a pharmacy for visitors of an older age group (elderly people over 65). The main problems in providing pharmaceutical care to elderly consumers in the local pharmaceutical market of a large metropolis (for example, Moscow) are identified. Positive and negative factors of consumer loyalty of elderly customers of Moscow pharmacies are indicated. The purpose of the study was to formulate a comprehensive socio-psychological portrait of an elderly consumer receiving pharmaceutical assistance in pharmacies in Moscow. In order to achieve this goal, a study of the behavior of visitors to pharmacies over 65 years of age, their sociological surveys, as well as a survey of pharmacy managers and employees to identify positive and negative factors that affect the consumer behavior of the studied focus group of customers, were conducted. A sociological survey of visitors to Moscow pharmacies and a survey of managers and employees of pharmacies revealed the positive and negative factors of consumer behavior of elderly consumers and identified the main problems encountered in pharmacies in the provision of pharmaceutical care for this category of patients. A comparative analysis of Russian and world experience in serving elderly visitors in pharmacies was carried out. The necessity of studying the behavior of consumers of older adult focus groups is proved in order to improve the quality of pharmaceutical and psychological care. Elderly clients (over 65) account for 40-65% of visitors to Moscow pharmacies. The consumer behavior of the studied category of patients is characterized by pronounced polypharmacy, the need for advisory services and psychological assistance, the need for communication, a significant lack of information about the assortment, the interaction of drugs, their correct use, and storage. The psychological and medical problems in most elderly patients complicate the process of providing them with timely and high-quality medical care; require the use of a special psychotherapeutic approach in the work of pharmacy employees, and the introduction of a specific “client-oriented pharmaceutical advising”.Keywords: Elderly patients; Elderly consumers; Older adults; Polypharmacy; Pharmaceutical assistance; Pharmacy organizations; Socio-psychological portrait; Client-oriented pharmaceutical advising.